Genetic Similarity between Ottoman Strawberry and the Other Early-Period Strawberry Cultivars Assessed by RAPD Markers - Doğan, H.; Akdaş, E. Y.; Uslu, Y. B.; Zengin, U.; ÇELİK, ÖZGE (Austin Publishing Group, 2017)
Most of the local strawberry (Fragaria x ananassa Duchenese) cultivars of Turkey are not phylogenetically classified. This present study, which aimed discriminating the genetical relationships between the Ottoman strawberry cultivar and other early-period strawberry cultivars planted in Istanbul and Karadeniz Ereğli regions of Turkey, is the first on this field. Seven strawberry cultivars were analyzed by using RAPD. 10 random primers carried out DNA fingerprinting analyses of these cultivars. The average polymorphism rate was determined as 87.1%. The most polymorphic primer was OPH01 which produced 13 bands. The cluster dendrogram presented that the similarity coefficients were between range of 0.03 and 0.73. Ottoman cultivar showed higher similarity with Tüylü more than Kara cultivar which is reported as the mother cultivar. RAPD method was sufficient to assess the phylogenetic relationship between Ottoman cultivar and other early-period strawberry cultivars. The data of this study brought forward the necessity of further genetic analysis to prove the phylogenetic relationship among Tüylü and Ottoman cultivars.
Keywords: RAPD; genetic similarity; Ottoman strawberry cultivar; Early-period strawberry